Cyanidin‐3‐glucoside binds to talin and modulates colon cancer cell adhesions and 3D growth. Issue 2 (9th January 2020) - Baster, Zbigniew; Li, Liqing; Kukkurainen, Sampo; Chen, Jing; Pentikäinen, Olli; Győrffy, Balázs; Hytönen, Vesa P.; Zhu, Haining; Rajfur, Zenon; Huang, Cai
Abstract: Cyanidin‐3‐glucoside (C3G) is a natural pigment, found in many colorful fruits and vegetables. It has many health benefits, including anti‐inflammation, cancer prevention, and anti‐diabetes. Although C3G is assumed to be an antioxidant, it has been reported to affect cell‐matrix adhesions. However, the underlying molecular mechanism is unknown. Here, we show that the expression of talin1, a key regulator of integrins and cell adhesions, negatively correlated with the survival rate of colon cancer patients and that depletion of talin1 inhibited 3D spheroid growth in colon cancer cells. Interestingly, C3G bound to talin and promoted the interaction of talin with β1A‐integrin. Molecular docking analysis shows that C3G binds to the interface of the talin‐β‐integrin complex, acting as an allosteric regulator and altering the interaction between talin and integrin. Moreover, C3G promoted colon cancer cell attachment to fibronectin. While C3G had no significant effect on colon cancer cell proliferation, it significantly inhibited 3D spheroid growth in fibrin gel assays. Since C3G has no or very low toxicity, it could be potentially used for colon cancer prevention or therapy.